Nitric Oxide in Plants: Metabolism and Role in Stress Physiology - Khan, M. Nasir; Mobin, Mohammad; Mohammad, Firoz; Corpas, Francisco J. (Springer International Publishing : Imprint: Springer, 2014)
This book covers the key features of nitric oxide (NO) in plants. Comprising nine chapters, Part I highlights its metabolism and identification in plants. Part II, which consists of eight chapters, focuses on the chemical, physical and biochemical properties of the NO molecule and its derivatives; on its functional role and mode of action; and on its signaling and interaction with phytohormones, mineral nutrients, biomolecules, ions and ion channels in plants under abiotic stresses. Combining the expertise of leading researchers in the field, the book provides a concise overview of plant NO biology and offers a valuable reference work.